2008
DOI: 10.1103/physreve.77.046120
|View full text |Cite
|
Sign up to set email alerts
|

Evolution equation for a model of surface relaxation in complex networks

Abstract: In this paper we derive analytically the evolution equation of the interface for a model of surface growth with relaxation to the minimum (SRM) in complex networks. We were inspired by Even though for Euclidean lattices the evolution equation is linear, we find that in complex heterogeneous networks non-linear terms appear due to the heterogeneity and the lack of symmetry of the network; they produce a logarithmic divergency of the saturation roughness with the system size as found by Pastore y Piontti et al. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 38 publications
5
37
0
Order By: Relevance
“…When the process reaches the steady state [20] of the evolution with this relaxation (R), we construct the gradient network and measure the pressure congestion J R after the relaxational dynamic is performed. In accordance with previous observations [20,22], the steady state is reached extremely quickly: the saturation time actually does not scale with the system size N but it approaches an N -independent constant [23,24].…”
supporting
confidence: 69%
“…When the process reaches the steady state [20] of the evolution with this relaxation (R), we construct the gradient network and measure the pressure congestion J R after the relaxational dynamic is performed. In accordance with previous observations [20,22], the steady state is reached extremely quickly: the saturation time actually does not scale with the system size N but it approaches an N -independent constant [23,24].…”
supporting
confidence: 69%
“…In Fig. 3 we plot W S as function of N in log-log scale for different values of p. We can see that for p = 0 there is a pure power law with exponent 0.186 (see Fig 1) and for p = 1 the scaling behavior of W s with N corresponds to a logarithm as expected for λ < 3 [24,25]. For values 0 < p < 1 we find that there is a crossover between both regimes.…”
mentioning
confidence: 78%
“…al. [25] who derived the evolution equation of this model on complex networks. However, up to our knowledge, neither the BD model nor the competition between different processes on complex networks was ever reported.…”
mentioning
confidence: 99%
“…More recently, research has focused on dynamical processes taking place on the underlying network [4][5][6][7][8][9][10]. Particularly, many mathematical and numerical models have been elaborated to study the problem of synchronization [11][12][13][14][15][16], a phenomenon present in the behavior of many collective systems. In these processes the state of the system evolves to a p-1 synchronized state, where the coupled units adjust their dynamics with one another.…”
mentioning
confidence: 99%
“…Solving the discrete EW equation numerically for finite size systems, in [12] the authors found that W s decreases with N , which is not representative of any growth model. With a different approach, La Rocca et al [14] developed a Langevin stochastic equation that describes the evolution of the interface, and solved it up to second order by numerical integration for finite system sizes, recovering Eq. (4).…”
mentioning
confidence: 99%